2016
DOI: 10.1111/jdv.13611
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival of biologic therapy in a large, disease‐based registry of patients with psoriasis: results from the Psoriasis Longitudinal Assessment and Registry (PSOLAR)

Abstract: Background Drug survival is a marker for treatment sustainability in chronic diseases such as psoriasis.ObjectiveThe aim of these analyses was to assess survival of biologic treatments in the PSOriasis Longitudinal Assessment and Registry (PSOLAR).Methods PSOLAR is a large, prospective, international, disease‐based registry of patients with psoriasis receiving (or eligible for) systemic therapy in a real‐world setting. Drug survival is defined as the time from initiation to discontinuation (stop/switch) of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
211
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(265 citation statements)
references
References 24 publications
38
211
2
14
Order By: Relevance
“…Table 3 summarizes all the studies published so far, where data were collected from large patient population of two or more centers, the follow-up period was at least one year, and the authors compared at least three or more biological therapies. The list includes five prospective registry-based studies and three retrospective studies (5,11,(16)(17)(18)(19)(20). Table 3 shows that those studies which included ustekinumab have found drug survival of ustekinumab superior to the drug survival of TNF-alpha inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarizes all the studies published so far, where data were collected from large patient population of two or more centers, the follow-up period was at least one year, and the authors compared at least three or more biological therapies. The list includes five prospective registry-based studies and three retrospective studies (5,11,(16)(17)(18)(19)(20). Table 3 shows that those studies which included ustekinumab have found drug survival of ustekinumab superior to the drug survival of TNF-alpha inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation may be previous therapeutic failure during infliximab treatment. Nevertheless, there are also reports that ustekinumab is effective in long-term therapy both in patients previously treated with biologics and taking ustekinumab as the first drug [22]. The study has also shown that ustekinumab is the drug which can be maintained for longer than other available drugs in patients with arthritic psoriasis.…”
Section: Discussionmentioning
confidence: 72%
“…ności tych leków podczas długotrwałego stosowania oraz że pewne grupy pacjentów gorzej odpowiadają na leczenie. W badaniach porównujących długotermi-nowe działanie i bezpieczeństwo leków biologicznych zauważono, że główną przyczyną przerywania terapii była utrata skuteczności leków [21][22][23][24]. W jednej z prac wzięło udział 1277 pacjentów leczonych ustekinumabem (anty-IL-12/IL-23), adalimumabem (anty-TNF-α), infliksymabem (anty-TNF-α) lub etanerceptem (białko fuzyjne -p75, ludzki receptor TNF-α połączony z Fc IgG1).…”
Section: Discussionunclassified
See 2 more Smart Citations